Geographical indication and artisanal cheeses: Legal Framework and challenges to a policy for this segment in Brazil - Valente da Cruz, Benedito Ely; Medeiros Hespanhol, Rosangela Ap. [UNESP] (Revues Org, 2018)
In recent years, artisanal cheeses have attracted the attention of researchers, governments, producers, and consumers of these delicacies in Brazil. The reasons for this awakening are related to a number of factors, such as : the contemporary crises in the agrifood sector; the valorization of the rural, as a synonym of the past, the traditional, nature, etc.; the (re) appreciation of traditional know-how seized as a possibility of access to safe food, when compared to industrialized products; and the perspective of territorial development. In this context of changes, the main objective of the research was to analyze the policy of Geographical Indications (GIs) in Brazil, focusing on the challenges related to the certification of artisanal cheeses, in particular the Cheeses of Serro and Canastra in Minas Gerais and of Marajo in Para. The research has a qualitative-quantitative approach in which bibliographic, documentary and field research were used, with application of semi-structured interview script. The theoretical reference was based on discussions on geographical indications, (re) territorialization and territorial development. As a result, the research identified that the lack of an adequate legal framework, the lack of understanding about GIs and the lack of a federal public policy for artisanal cheeses are the major challenges for this segment in Brazil.
Keywords: Artisanal Cheeses; Geographical Indication; Legal framework; Territorial development